Determination Analysis of Hospitals in East Java on Readiness in Facing a Pandemic Based on the WHO Rapid Hospital Readiness Checklist - Atok Irawan; Sentot Imam Suprapto; Wardani, Ratna (Universitas STRADA Indonesia, 2023)
Background: During the COVID-19 pandemic, health service providers, especially hospitals, are expected to be able to optimize all their resources in providing services to patients. Assessment of hospital readiness in dealing with the COVID-19 pandemic is needed to ensure that hospitals continue to maintain and improve the quality of health services and patient safety. Purpose: The purpose of this study was to analyze the effect of hospital classification, type of service, referral status and accreditation status on hospital readiness in dealing with the COVID-19 pandemic in East Java. Methods: The design of this study is a quantitative observational analytic type with a cross sectional approach. The population of this study is 385 hospitals in East Java. The sampling technique of probability sampling with a stratified random sampling approach obtained a sample of 129 hospitals. The data analysis used is Dummy Multiple Linear Regression. Results: The results showed that the classification of the hospital with a p value = 0.001 and the accreditation status with a p = 0.000 had an effect on the readiness of the hospital to face a pandemic. Meanwhile, the type of service with a p value = 0.397 and referral status with a p value = 0.077 did not affect the readiness of the hospital to face a pandemic. Conclusion: Hospital classification and accreditation status influence hospital readiness to face the COVID-19 pandemic in East Java. Therefore, regular monitoring and evaluation of readiness to face a pandemic is important for all hospitals to carry out through independent assessments. Making efforts to improve each component, especially in class C and D hospitals, as well as collaborating with the Health Service is very necessary to fulfill regulations and implement improved services for both COVID-19 and non-COVID-19 patients.